Edible bird nest shape quality assessment using machine vision system - Fathinul Syahir, Ahmad Sa'ad; Ali Yeon, Md Shakaff, Prof. Dr.; Ammar, Zakaria; Mohd Zulkifly, Abdullah, Dr.; Abdul Hamid, Adom, Prof. Dr; Ezanuddin, A. A. M. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org